To find the missing value, we need to simplify the left side of the equation first by expanding the product on the left side.
8y^6(8y^9 + ? + 9y^2) = 64y^15 + 32y^12 + 72y^8
When we distribute 8y^6 to the terms inside the parentheses, we get:
64y^15 + 8y^6 * ? + 72y^8 = 64y^15 + 32y^12 + 72y^8
Now we can simplify the equation by comparing the coefficients of like terms.
From the equation, we can see that:
8y^6 * ? = 32y^12
Dividing both sides by 8y^6, we get:
? = 4y^6
Therefore, the missing value is 4y^6.
Find the missing value: Click Here for Help Video 8 𝑦 6 ( 8 𝑦^9 + ? + 9 𝑦^2 ) = 64 𝑦^15 + 32 𝑦^12 + 72 𝑦^8
1 answer